Nachshon, who was afraid to swim : a Passover story - Cohen, Deborah Bodin, 1968-; Jago (Minneapolis : Kar-Ben Pub., 2009)
When the Israelites flee Egypt, Nachshon exhibits great courage by being the first to step into the Red Sea, even though he cannot swim.
Publisher's Weekly.
School Library Journal.
Wilson's Children.
4.5
K-3
Keywords: Bible -- History of Biblical events -- Fiction; Courage -- Juvenile fiction; Fear -- Juvenile fiction; Slavery -- Juvenile fiction; Courage -- Fiction; Fear -- Fiction; Slavery -- Fiction; Bible fiction; Courage -- Fiction; Fear -- Fiction; Slavery -- Fiction